Bilateral motor priming for post stroke upper extremity hemiparesis: A randomized pilot study - Stoykov, Mary Ellen (Restor Neurol Neurosci, 2020)
BACKGROUND: Bilateral priming, device assisted bilateral symmetrical wrist flexion/extension, is a noninvasive neuromodulation technique that can be used in the clinic. OBJECTIVE: We examined the additive effect of bilateral motor priming and task specific training in individuals with severe upper limb hemiparesis. METHODS: This is a parallel assignment, single-masked, randomized exploratory pilot study with three timepoints (pre-/post-intervention and follow up). Participants received either bilateral motor priming or health care education followed by task specific training. Sixteen participants who were at least 6 months post-stroke and had a Fugl Meyer Upper Extremity (FMUE) score between 23 and 38 were randomized. Our primary and secondary measures were Chedoke Arm & Hand Activity Index 9 (CAHAI-9) and the FMUE respectively. We determined changes in interhemispheric inhibition using transcranial magnetic stimulation. We hypothesized that improvement in the priming group would persist at follow up. RESULTS: There was no between-group difference in the CAHAI. The improvement in the FMUE was significantly greater in the experimental group at follow up (t = 2.241, p = 0.045). CONCLUSIONS: Both groups improved in the CAHAI. There was a significant between-group difference in the secondary outcome measure (FMUE) where the bilateral priming group had an average increase of 10 points from pre-intervention to follow up.